A Basic Germanodecatungstate with a −7 Charge: Efficient Chemoselective Acylation of Primary Alcohols1. Issue 48 (26th September 2014) - Sugahara, Kosei; Satake, Naoto; Kamata, Keigo; Nakajima, Takahito; Mizuno, Noritaka
Abstract The synthesis of highly negatively charged polyoxometalates with electrically and structurally controlled uniform basic sites can lead to the unique base catalysis. In this work, a γ‐Keggin germanodecatungstate, [γ‐HGeW10O36]7− (A), having a −7 charge was, for the first time, successfully synthesized by the reaction of [γ‐H2GeW10O36]6− with one equivalent of [(n‐C4H9)4N]OH under non‐aqueous conditions. The activities of germanodecatungstates for base‐catalyzed reactions dramatically increased with increase in the number negative charges from −6 to −7. In the presence of A, various combinations of acylating agents and primary alcohols including those with acid‐sensitive functional groups chemoselectively gave the desired acylated products in high yields even under the stoichiometric conditions.